Indoor Air Pollution Associated with Household Fuel Use in India : An Exposure Assessment and Modeling Exercise in Rural Districts of Andhra Pradesh, India - Balakrishnan, Kalpana; Mehta, Sumi; Kumar, Priti; Ramaswamy, Padmavathi; Sambandam, Sankar; Kumar, Kannappa Satish; Smith, Kirk R. (World Bank, Washington, DC, 2014)
Indoor air pollutants associated with combustion of solid fuels in households of developing countries are now recognized as a major source of health risks to the exposed populations. Based on this background, the present study was designed with three major objectives: to monitor household pollution concentrations in a statistically representative rural sample in southern India; to model household indoor air pollution levels based on information on household-level parameters collected through questionnaires, in order to determine how well such survey information could be used to estimate air pollution levels without monitoring; and to record time/activity and other information at the household-level, in order to estimate the exposures of different household members. This paper contains the following headings: background, study design and methodology, results, and conclusions.